Passion according to St. Luke : (1779) - Bach, Carl Philipp Emanuel 1714-1788; Homilius, Gottfried August 1714-1785; Benda, Jiří 1713-1752; Stölzel, Gottfried Heinrich 1690-1749; Telemann, Georg Philipp 1681-1767; Exner, Ellen (Los Altos, California : The Packard Humanities Institute, 2016)
Like the 1771 Passion, the 1779 St. Luke Passion is a pasticcio crafted by Bach mostly from pre-existing works by other composers. It uses recitatives originally by Telemann to convey the biblical narrative and weaves in expressive movements borrowed and adapted by Bach to fit the context of the gospel narrative.
General preface -- Preface: passions -- Introduction -- Libretto -- Plates -- Passions-music nach dem Evangelisten Lucas (H 792, BR-CPEB D 6.2) -- Abbreviations -- Critical report -- Sources -- Commentary -- Appendix: Georg Benda, "Ich seh hinab ins traurige Gefilde."
For vocal soloists (SATB), chorus (SATB), and orchestra (2 horns, 2 flutes, 2 bassoons, violin I-II concertato, violin I-II, viola, and continuo (cello and organ)).
Original performance forces probably consisted of only 15 players for the instruments and 8 singers for the vocal ensemble, using two voices in each range for the choruses, with the solo parts divided between the singers in the ensemble.
Recitatives generally by Telemann, with music for non-recitative sections borrowed from sacred works by Homilius (HoWV I.4 and II.72), Benda (L 515, 542, and 548) and Stölzel (Passion oratorio Sechs geistliche Betrachtungen des leidenden und sterbenden Jesu); C.P.E. Bach probably only composed no. 6, 21, and 22.
Figured bass unrealized.
Includes preface and critical report.
German words; libretto also printed separately as text (pages xix-xxiii).
Keywords: Passion; Oratorio; Libretto